E-Commerce on Reserve: Opportunities, Challenges, and Taxation - Buchan, Alexander E. (Journal of Aboriginal Economic Development, 2018)
This paper provides an overview of the law relating to the taxation of income stemming from e-commerce on Indian reserves. The paper seeks to identify the opportunities and limitations for e-commerce on reserve, including the specific tax implications for bands, corporations, and individuals, and the practical barriers for Indigenous communities that wish to engage in e-commerce, such as infrastructure and capacity gaps.